A Synopsis of the "Influence of Epigenetics, Genetics, and Immunology" Session Part A at the 35th Annual Society of Toxicologic Pathology Symposium. (January 2017) - Harrill, Alison H.; Moggs, Jonathan G.; Adkins, Karissa K.; Augustin, Hellmut G.; Johnson, Robert C.; Leach, Michael W.
The overarching theme of the 2016 Society of Toxicology Pathology's Annual Symposium was "The Basis and Relevance of Variation in Toxicologic Responses." Session 4 focused on genetic variation as a potential source for variability in toxicologic responses within nonclinical toxicity studies and further explored how knowledge of genetic traits might enable targeted prospective and retrospective studies in drug development and human health risk assessment. In this session, the influence of both genetic sequence variation and epigenetic modifications on toxicologic responses and their implications for understanding risk were explored. In this overview, the presentations in this session will be summarized, with a goal of exploring the ramifications of genetic and epigenetic variability within and across species for toxicity studies and disseminating information regarding novel tools to harness this variability to advance understanding of toxicologic responses across populations.